Needle Stick and Sharp Objects Injuries Infection Prevention and Control Guidelines among Health Care Students: Descriptive, Cross Sectional Study - Mohsen, Dalia M.; Dogham, Rawhia; Ghaly, Asmaa Saber (International Journal of Innovative Research in Medical Science, 2019)
Background: Percutaneous exposure to contaminated needle sticks and other sharps is a danger not only to health care workers but also to nursing and paramedical students that increases the morbidity and mortality from infections with blood borne pathogens. Knowledge concerning the general precautions is vital for the prevention of such accidents. This study aimed to describe the knowledge and practice of infection prevention and control guidelines among health care students regarding needle stick and sharp objects injuries. Methods: A descriptive, cross sectional research design was used. Health care students were selected using convenience sampling which included 90 students. Data was collected using a self-reporting structured online questionnaire and administered to a number of health care students including nursing and Clinical laboratory specialists. Results: It was found that about half (49%, 52%) of the students had fair knowledge and fair practice regarding needle stick injuries and infection control guidelines respectively. The majority of the students (76.7%) had positive attitudes towards Needle stick injuries and infection control guidelines. Conclusion: This study concluded that knowledge and practice of health care students about the risk associated with needle-stick and sharp objects injuries and use of preventive measures was fair. Special concerns should be given to the role of post exposure prophylaxis, the recapping of needles and the importance and mechanism of reporting NSIs. Standing operating procedures should be conveyed regarding needle-stick and sharp objects injuries in all the health facilities.